Strengthening Digital Marketing of Ajakkang Local Products through the LESTARI System to Support Community Empowerment: Penguatan Pemasaran Digital Produk Lokal Ajakkang Berbasis Sistem LESTARI untuk Mendukung Pemberdayaan Masyarakat - Nurwati Djam'an; Suradi Tahmir; Andi Ihsan; Heri Tahir; Fitriwati Djam'an (Yayasan Ahmar Cendekia Indonesia, 2026)
This community service program aims to strengthen the digital marketing of local products through the implementation of the LESTARI System as a community-based digital marketing platform. The program was conducted during the odd semester of the 2025/2026 Academic Year through a collaborative initiative involving lecturers and students from Universitas Negeri Makassar and Universitas Hasanuddin. The program was implemented in Ajakkang Village, Soppeng Riaja District, Barru Regency, involving the Fish Processing Group (POKLAHSAR) Berkah, local MSME actors, and the village government. The implementation method employed a Participatory Action Research (PAR) approach through stages of problem identification, needs analysis, system development, community training and mentoring, system implementation, and program evaluation. The results demonstrated an improvement in community capacity in digital marketing, business management, product branding, and the utilization of social media and marketplaces as promotional media. The implementation of the LESTARI System also encouraged increased community participation, the emergence of local leaders, and greater public awareness regarding the importance of digital transformation and mangrove environmental conservation as part of sustainable economic development. Therefore, the LESTARI System has proven effective as a medium for strengthening the digital marketing of local products while supporting technology-based empowerment of coastal communities. Abstrak Kegiatan pengabdian masyarakat ini bertujuan untuk memperkuat pemasaran digital produk lokal melalui implementasi Sistem LESTARI sebagai platform pemasaran digital berbasis komunitas. Kegiatan ini dilaksanakan pada semester ganjil Tahun Akademik 2025/2026 dengan melibatkan kolaborasi dosen dan mahasiswa dari Universitas Negeri Makassar dan Universitas Hasanuddin. Program dilaksanakan di Desa Ajakkang, Kecamatan Soppeng Riaja, Kabupaten Barru, dengan melibatkan Kelompok Pengolah Hasil Perikanan (POKLAHSAR) Berkah, pelaku UMKM lokal, dan pemerintah desa. Metode pelaksanaan menggunakan pendekatan Participatory Action Research (PAR) melalui tahapan identifikasi masalah, analisis kebutuhan, pengembangan sistem, pelatihan dan pendampingan masyarakat, implementasi sistem, serta evaluasi program. Hasil kegiatan menunjukkan adanya peningkatan kapasitas masyarakat dalam pemasaran digital, pengelolaan usaha, branding produk, serta pemanfaatan media sosial dan marketplace sebagai sarana promosi. Implementasi Sistem LESTARI juga mendorong peningkatan partisipasi masyarakat, tumbuhnya penggerak lokal (local leader), serta meningkatnya kesadaran masyarakat terhadap pentingnya transformasi digital dan pelestarian lingkungan mangrove sebagai bagian dari pembangunan ekonomi berkelanjutan. Dengan demikian, Sistem LESTARI terbukti efektif sebagai media penguatan pemasaran digital produk lokal sekaligus mendukung pemberdayaan masyarakat pesisir berbasis teknologi.